2021
DOI: 10.1111/1462-2920.15431
|View full text |Cite
|
Sign up to set email alerts
|

Impact of manipulation of glycerol/diol dehydratase activity on intestinal microbiota ecology and metabolism

Abstract: Glycerol/diol dehydratases (GDH) are enzymes that catalyse the production of propionate from 1,2-propanediol, and acrolein from glycerol. Acrolein reacts with dietary carcinogenic heterocyclic amines (HCA), reducing HCA mutagenicity, but is itself also an antimicrobial agent and toxicant. Gut microbial GDH activity has been suggested as an endogenous acrolein source; however, there is limited information on the potential of the intestinal microbiota to have GDH activity, and what impact it can have on the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 53 publications
(108 reference statements)
5
24
0
Order By: Relevance
“…Indeed, the potential for GDH metabolism is a common feature of human intestinal microbiota shared by a few taxa including A. hallii, F. plautii, and B. obeum. 28,34 In this study, we found that acrolein was produced by the tested WT S. Typhimurium strains, as revealed by the transformation of the acrolein probe PhIP. The transformation capacity varied over 10-fold for the different strains.…”
Section: ■ Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Indeed, the potential for GDH metabolism is a common feature of human intestinal microbiota shared by a few taxa including A. hallii, F. plautii, and B. obeum. 28,34 In this study, we found that acrolein was produced by the tested WT S. Typhimurium strains, as revealed by the transformation of the acrolein probe PhIP. The transformation capacity varied over 10-fold for the different strains.…”
Section: ■ Discussionmentioning
confidence: 74%
“…plautii, and B. obeum. , In this study, we found that acrolein was produced by the tested WT S. Typhimurium strains, as revealed by the transformation of the acrolein probe PhIP. The transformation capacity varied over 10-fold for the different strains.…”
Section: Discussionmentioning
confidence: 99%
“…The high microbiota to medium ratio was chosen to enable the evaluation of the microbial biotransformation of the compounds and impact of the compounds on microbial viability under limited growth. The nutritive medium was based on the Macfarlane medium for the cultivation of human colon microbiota [20] and contained (in g/L): cellobiose (1); oat xylan (1); larch wood arabinogalactan (1); inulin (0.5); soluble potato starch (1); amicase (3); meat extract (1.5); mucin (4); tryptone (5); yeast extract (4.5); bile salts (0.4); KH 2 PO 4 (3); NaHCO 3 (9) (20); folic acid (20); cyanocobalamin (5); thiamine (50); riboflavin (50); phylloquinone (0,075); menadione (10); pantothenate (100). Single compounds or plant extracts were added to 10 mL microbiota mixture, at a final concentration of 30 µg/mL or 500 µg/mL, respectively.…”
Section: Anaerobic Batch Fermentation Experiments With Herbal and Syn...mentioning
confidence: 99%
“…In vitro human gut microbiota models inoculated with fecal microbiota and mimicking the physicochemical conditions of the gut are powerful tools to evaluate the xenobiotic-microbiota interactions [10,11]. We previously showed that the artificial microbiota produced with the PolyFermS model inoculated with immobilized fecal microbiota is a reproducible source of large amounts of inocula for high throughput testing and comparison of different treatment conditions, including xenobiotic degradation with the same microbiota background [10,12]. A particular advantage of using the latter is that the amount of inoculum is not limiting and high inoculation ratios (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation